Brain Transforming Growth Factor-β Resists Hypertension Via Regulating Microglial Activation. Issue 9 (September 2017) - Li, You; Shen, Xiao Z.; Li, Liang; Zhao, Tuantuan V.; Bernstein, Kenneth E.; Johnson, Alan K.; Lyden, Patrick; Fang, Jianmin; Shi, Peng
Abstract : Background and Purpose—: Hypertension is the major risk factor for stroke. Recent work unveiled that hypertension is associated with chronic neuroinflammation; microglia are the major players in neuroinflammation, and the activated microglia elevate sympathetic nerve activity and blood pressure. This study is to understand how brain homeostasis is kept from hypertensive disturbance and microglial activation at the onset of hypertension. Methods—: Hypertension was induced by subcutaneous delivery of angiotensin II, and blood pressure was monitored in conscious animals. Microglial activity was analyzed by flow cytometry and immunohistochemistry. Antibody, pharmacological chemical, and recombinant cytokine were administered to the brain through intracerebroventricular infusion. Microglial depletion was performed by intracerebroventricular delivering diphtheria toxin to CD11b-diphtheria toxin receptor mice. Gene expression profile in sympathetic controlling nucleus was analyzed by customized qRT-PCR array. Results—: Transforming growth factor-β (TGF-β) is constitutively expressed in the brains of normotensive mice. Removal of TGF-β or blocking its signaling before hypertension induction accelerated hypertension progression, whereas supplementation of TGF-β1 substantially suppressed neuroinflammation, kidney norepinephrine level, and blood pressure. By means of microglial depletion and adoptive transfer, we showed that the effects of TGF-β on hypertension are mediated through microglia. In contrast to the activated microglia in established hypertension, the resting microglia are immunosuppressive and important in maintaining neural homeostasis at the onset of hypertension. Further, we profiled the signature molecules of neuroinflammation and neuroplasticity associated with hypertension and TGF-β by qRT-PCR array. Conclusions—: Our results identify that TGF-β–modulated microglia are critical to keeping brain homeostasis responding to hypertensive disturbance. Abstract : Supplemental Digital Content is available in the text.